Design of “Munyer” as a Respons to Social Condition in New Normal - Warsana, Warsana; Irawati, Eli (Institut Seni Indonesia Yogyakarta, 2023)
This study aimed to observe social background of “Munyer” masterpiece creation. This study was a qualitative study through library research, observation and interview to elaborate the composition. The finding showed that the design method consisted of initial stimulation, idea generation, exploration, improvisation, formation and presentation or performance. The result of this design was a new musical masterpiece with instruments, pattern and performance in five composition parts. Each part illustrates online learning situation happened in New Normal. Thus, the creation of “munyer” was a response to social condition in new normal where all pedagogical activities were conducted via online. However, there were complex obstacles and problems during online classes such as poor provider network, massive internet data plan, non-updated hardware and software, etc.